Experimental study of the bio-additives in biodiesel fuel on performance and emissions characteristics of diesel engine - Abd Hadi, Syahrunniza (2015)
Among the alternative fuels the Bio diesel is one the most common and familiar to all. It’s biodegradable, environment friendly as well as suitable source, to meet the future energy crises. The main concern of this experimental analysis is to reach a tentative goal, how this fuel can be utilised with maximum effective way. To find this ,an experiment data analysis of different parameter such as break power, break mean effective pressure consumption, emission characteristic (NOx, HC,CO. etc.), is done through bio diesel fuel and also compared with ordinary diesel which is also known as standard diesel. Despite years of improvement attempts, the key issue in using bio based fuels is oxidation stability, stoichiometric point, bio-fuel composition, antioxidants on the degradation and much oxygen with comparing to diesel gas oil. Thus, the improvement of emission exhausted from diesel engines fuelled by biodiesel is urgently required to meet the future stringent emission regulations. This investigation is carried out through 20 HP eddy current dynamometer and load cell arrangement which is controlled by a DYNOMAXtm software computer in case of finding the break power and BMEP respectively. And the emission characteristics are observed using Airrex HG-540 exhaust analysers finally the result is compared with diesel engine which is run by standard diesel. Di Methyl Poly siloxane (DMPS) additive and D20 palm oil methyl formula was used in this studies. The final result implied that the bio diesel with some additives with (CP10+DMPS Power) and (JC15+ DMPS) shows best performance and reduce the exhaust emission including CO. Thus the decision may be taken, 10% - 15% blended bio diesel with DMPS additive as a best alternative fuel considering all the view aspects and alternatives.